Marine Skeletons: Towards Hard Tissue Repair and Regeneration - Innocent J. Macha; Besim Ben-Nissan (Marine Drugs, 2018)
Musculoskeletal disorders in the elderly have significantly increased due to the increase in an ageing population. The treatment of these diseases necessitates surgical procedures, including total joint replacements such as hip and knee joints. Over the years a number of treatment options have been specifically established which are either permanent or use temporary natural materials such as marine skeletons that possess unique architectural structure and chemical composition for the repair and regeneration of bone tissue. This review paper will give an overview of presently used materials and marine structures for hard tissue repair and regeneration, drugs of marine origin and other marine products which show potential for musculoskeletal treatment.